Antibacterial activity of new hydrophilic sealants: In vitro study - Federica Veneri; Elena Bardellini; Francesca Amadori; Emanuela Gobbi; Raffaella Belotti; Alessandra Majorana (Wolters Kluwer Medknow Publications, 2020)
Background: Pits and fissures sealing and modulation of oral microbiota through probiotics are important preventive measures against dental decays. The aim of this study was to investigate the antibacterial activity of the Embrace™ WetBond™ Pit and Fissure Sealant (Pulpdent, USA) and UltraSeal XT® Hydro™ (Ultradent, USA) against selected oral bacteria and probiotics. Methods: The antibacterial effect of both sealants was tested both through planktonic growth inhibition test - 96-well microtiter plates and agar disk diffusion assay containing light-cured Embrace™ and UltraSeal XT® against Streptococcus mutans and two oral probiotics (Streptococcus salivarius and Lactobacillus reuteri). Results: Embrace™ showed a stronger and broad activity against all the bacterial strains tested (P < 0.05) in planktonic growth inhibition test even at its lowest dose (10 μl), with inhibition rates higher than 90% in all cases. UltraSeal XT® Hydro™ showed a mild antibacterial activity against L. reuteri, with growth inhibition rates being 19% and 23% for 20 μl and 50 μl, respectively. Regarding agar disk diffusion test, both sealants showed exclusively an antibacterial activity by contact. Conclusions: According to these findings, it is recommended to carefully plan the timing for the administration of different preventive interventions, such as oral probiotics assumption and sealant application, to maximize their specific effectiveness. We suggest prescribing oral probiotics first and putting off the Embrace™ sealant application to the end of probiotic treatment. On the contrary, it is possible to administer L. reuteri simultaneously with the application of UltraSeal XT® since it elicits a minimal antibacterial action against this oral probiotic.